Gas and Dust Measurements for Taylor Glacier and Taylor Dome Ice Cores - Baggenstos, Daniel; Barker, Stephen; Bauska, Thomas; Brook, Edward J; Dyonisius, Michael; Marcott, Shaun; Mcconnell, Joseph; Menking, James; Petrenko, Vasilii; Rhodes, Rachel; Severinghaus, Jeffrey; Shackleton, Sarah (IEDA: US Antarctic Program Data Center, 2019)
Abstract: New ice cores retrieved from the Taylor Glacier (Antarctica) blue ice area contain ice and air spanning the Marine Isotope Stage (MIS) 5-4 transition, a period of global cooling and ice sheet expansion. We determine chronologies for the ice and air bubbles in the new ice cores by visually matching variations in gas- and ice- phase tracers to preexisting ice core records. The chronologies reveal an ice age-gas age difference (Δage) approaching 10 ka during MIS 4, implying very low snow accumulation in the Taylor Glacier accumulation zone. A revised chronology for the analagous section of the Taylor Dome ice core (84 to 55 ka), located to the south of the Taylor Glacier accumulation zone, shows that Δage did not exceed 3 ka. The difference in Δage between the two records during MIS 4 is similar in magnitude but opposite in direction to what is observed at the Last Glacial Maximum. This relationship implies that a spatial gradient in snow accumulation existed across the Taylor Dome region during MIS 4 that was oriented in the opposite direction of the accumulation gradient during the Last Glacial Maximum.